Chemokine Gene Expression in Astrocytes of Borna Disease Virus-Infected Rats and Mice in the Absence of Inflammation - Sauder, Christian (American Society for Microbiology, 2000)
Borna disease virus (BDV) causes CD8(+) T-cell-mediated meningoencephalitis in immunocompetent mice and rats, thus providing a valuable animal model for studying the mechanisms of virus-induced central nervous system (CNS) immunopathology. Chemokine-mediated leukocyte recruitment to the CNS is a crucial step in the development of neurological disease. We found increased mRNA levels of IP-10 and other chemokines in brains of adult rats following infection with BDV. The marked increase in chemokine gene expression at about day 8 postinfection seemed to immediately precede the inflammatory process. In brains of rats infected as newborns, in which inflammation was only mild and transient, sustained expression of IP-10 and RANTES genes was observed. In situ hybridization studies revealed that astrocytes were the major source of IP-10 mRNAs in brains of rats infected as newborns and as adults. In brains of infected mice lacking CD8(+) T cells (β2m(0/0)), transcripts encoding IP-10 and RANTES were also observed. IP-10 transcripts were also present in a small number of scattered astrocytes of infected knockout mice lacking mature B and T cells as well as functional alpha/beta and gamma interferon receptors, indicating that BDV can induce chemokine synthesis in the absence of interferons and other B- or T-cell-derived cytokines. These data provide strong evidence that CNS-resident cells are involved in the early localized host immune response to infection with BDV and support the concept that chemokines are pivotal for the initiation of virus-induced CNS inflammation.